1991
DOI: 10.1111/j.1600-0447.1991.tb05526.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing personality disorders in psychiatric inpatients

Abstract: This study investigated assumptions made by DSM-III and DSM-III-R regarding Axis I-Axis II associations and sex differences for the 11 personality disorders (PD). A total of 112 patients formed 4 Axis I diagnostic groups: recent-onset schizophrenia (n = 35); recent-onset mania (n = 26); unipolar affective disorder (n = 30); and a mixed diagnostic group (n = 21). The prevalence of PD was determined using the Structured Interview for DSM-III Personality Disorders (SIDP). Schizophrenia was associated with antisoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…Several clinical studies have tested for sex differences in DSM personality disorders (Jackson et al 1991 ;Golomb et al 1995 ;Grilo et al 1996 ;Carter et al 1999 ;Grilo, 2002) but only one (Carter et al 1999) found a sex difference, the prevalence being unexpectedly higher in men. Results from non-clinical studies are also inconsistent ; some reported higher prevalence rates in women (Zimmerman & Coryell, 1989), others in men (Samuels et al 2002 ;Coid et al 2006), while the only large representative populationbased study (Torgersen et al 2001) did not find sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have tested for sex differences in DSM personality disorders (Jackson et al 1991 ;Golomb et al 1995 ;Grilo et al 1996 ;Carter et al 1999 ;Grilo, 2002) but only one (Carter et al 1999) found a sex difference, the prevalence being unexpectedly higher in men. Results from non-clinical studies are also inconsistent ; some reported higher prevalence rates in women (Zimmerman & Coryell, 1989), others in men (Samuels et al 2002 ;Coid et al 2006), while the only large representative populationbased study (Torgersen et al 2001) did not find sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…Of those studies employing structured interviews and reporting on the proportion of subjects with a mood disorder who also have a personality disorder [Reich and Noyes, 1987;Alnaes and Torgersen, 1988;Zimmerman and Coryell, 1989;Jackson et al, 1991;Markowitz et al, 1992;Sanderson et al, 1992;Golomb et al, 1995;Pepper et al, 1995;Fava et al, 1996;Alpert et al, 1997], estimates range from 18% to 95%, with patients with dysthymic disorder having somewhat higher rates of personality disorder (PD) comorbidity than patients with major depressive disorder (MDD). Avoidant, dependent, and borderline personality disorders have been most common, but not necessarily most discriminating with respect to a comparison group.…”
Section: Introductionmentioning
confidence: 97%
“…Only 15 studies have employed recognized structured or semistructured interviews to assess a range of Axis I and Axis II disorders [Dahl, 1986;Reich and Noyes, 1987;Alnaes and Torgersen, 1988;Zanarini et al, 1989Zanarini et al, , 1998Zimmerman and Coryell, 1989;Jackson et al, 1991;Markowitz et al, 1992;Sanderson et al, 1992;Coid, 1993;Golomb et al, 1995;Oldham et al, 1995;Pepper et al, 1995;Fava et al, 1996;Alpert et al, 1997]. Differences in sample composition (i.e., inpatients, outpatients, criminals, and nonpatients) and focus on current or lifetime disorders account for additional variation.…”
Section: Introductionmentioning
confidence: 98%
“…11,38 In our review, borderline PD was the most frequent comorbid PD in bipolar patients, with a rate of 10%, tenfold that observed in the general population. 39 However, reported rates varied broadly, ranging from 6.2 to 30% in BD type I 7,[19][20][21]40 and 12 to 23% in BD type II. 16,41,42 On the other hand, comorbid antisocial PD was very infrequent in the studies included in our review (0.79%), and seems to be more common in BD type I than in type II.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, rates up to 73.6% 21,22 have been found, especially when evaluating hospitalized or highly symptomatic patients. Additionally, variability may also be due to methodological differences, such as instruments used, phase of the disease at the time of data collection, and criteria for euthymia.…”
mentioning
confidence: 99%